Technology as system innovation: a key informant interview study of the application of the diffusion of innovation model to telecare. (January 2014) - Sugarhood, Paul; Wherton, Joseph; Procter, Rob; Hinder, Sue; Greenhalgh, Trisha
Abstract Purpose: To identify and explore factors that influence adoption, implementation and continued use of telecare technologies. Method: As part of the Assistive Technologies for Healthy Living in Elders: Needs Assessment by Ethnography (ATHENE) project, 16 semi-structured interviews were conducted with key participants from organisations involved in developing and providing telecare technologies and services. Data were analysed thematically, using a conceptual model of diffusion of innovations. Results: Participants identified numerous interacting factors that facilitated or hindered adoption and use. As predicted by the model, these related variously to the technology, individual adopters, the process of social influence, the innovativeness and readiness of organisations, implementation and routinisation processes following initial adoption, and the nature and strength of linkages between these elements. Key issues included (i) the complexity and uniqueness of the "user system", (ii) the ongoing work needed to support telecare use beyond initial adoption, and (iii) the relatively weak links that typically exist between users of telecare technologies and the organisations who design and distribute them. Conclusions: Telecare is not merely a technology but a complex innovation requiring input from, and coordination between, people and organisations. To promote adoption and use, these contextual factors must be specified, understood and addressed. Implications for Rehabilitation Telecare should not be thought of as a "plug and play" technology but as a complex innovation requiring input from, and coordination between, people and organisations. To promote adoption and use of telecare, a number of contextual factors must be specified, understood and addressed. End users and other stakeholders should be linked at the earliest stages of design and development. Such co-production should aim to identify how technologies might better fit with users' material surroundings, social networks and desired lifestyles, rather than being technology-driven and focused on proof of concept or usability.